ANALISIS KEPASTIAN HUKUM TEHADAP PERSEKONGKOLAN DALAM TENDER PADA PUTUSAN KPPU NOMOR 10/KPPU-I/2017 - Ichsan Saputro (2022)
One form of violation in business competition that can hinder economic activity and harm others is conspiracy. This conspiracy is regulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Unfair business competition itself is competition between business actors in carrying out production and or marketing activities of goods and or services that is carried out dishonestly or against the law or hinders business competition. Unfair business competition in tender conspiracy is caused by an imbalance between market opportunities and the number of business actors. Conspiracy is a form of cooperation carried out by business actors with other business actors with the intention of controlling the relevant market for the interests of the conspiring business actors. So that the business actor who commits the conspiracy gets its own advantage and other business actors are harmed by the actions of the conspiracy. The purpose of this study was to analyze the existence of conspiracy in the tender and legal certainty in the construction project of the Mandala Krida stadium in the case decision number 10/KPPU-I/2017. The type of research used is normative juridical law research, which uses various primary, secondary, and tertiary legal sources, through statutory approaches and case approaches, with library research data collection techniques and uses qualitative juridical analysis. The results of this study are able to find out legal certainty and how the tender conspiracy can be carried out on the Mandala Krida stadium construction project in case decision number 10/KPPU-I/2017. Suggestions in this research are needed to amend Law No. 5/1999 where the KPPU's evidence is carried out against conspiracy in tenders using the rule of reason and per se illegal. In addition, this approach allows for business certainty, efficiency in the litigation process and as a tool to prevent the impact of competition, meaning that this approach is cost-effective in the litigation process, administrative costs and other juridical sources. Meanwhile, for the KPPU to determine the value of the fine, it is better to first describe the factors that are used as the basis for calculating the fine and detail the process of calculating the fine, in accordance with the mandate of the law.